Pengaruh Discovery Learning Terhadap Aktivitas Belajar Siswa Pada Pembelajaran Penjas Siswa Kelas VIII di SMPN 1 Telukjambe Timur - Reza Andriana; Fahrudin Fahrudin; Rahmat Iqbal (Peneliti.net, 2023)
The purpose of this study was conducted to determine whether there was an influence or not in the discovery learning model on physical education learning activities for class VIII at SMPN 1 Telukjambe Timur. This study uses a descriptive quantitative approach with experimental methods. This research was conducted at SMPN 1 Telukjambe Timur with a sample of class VIII A, which consisted of 38 students. The instrument used was a questionnaire for learning physical education activities. Data processing techniques using hypothesis testing (T-Test). The results of this study indicate that the discovery learning learning model influences physical education learning activities in class VIII A students at SMPN 1 Telukjambe Timur. The results of the calculations that have been done show that the pretest questionnaire has an average value of 106.87 while the posttest value has a higher value with an average value of 120.79. as well as the value of the paired sample test using sig (2-tailed) which is equal to 0.000 where the value is <0.05 then Ho is rejected and Hi is accepted indicating that there is a difference between the initial variable and the final variable this shows that there is a significant influence on differences in the treatment given to each variable. This can be seen in the unfavorable category of 42% (16 students), quite good category of 45% (17 students), and very good category of 13% (5 students). Thus it can be concluded that the Discovery Learning learning model has an effect on physical education learning activities for Grade VIII students at SMPN 1 Telukjambe Timur in a